SIMULASI PERGERAKAN TUMPAHAN MINYAK DI LAUT DENGAN PENGARUH ANGIN - Millah, Nashrul; Anggriani, Indira; Nugraheni, Kartika (SPECTA Journal of Technology, 2019)
As a petroleum-producing country, Indonesia has a very important role in supplying national and international petroleum needs. The distribution of oil by sea raises the risk of spills and harms the marine environment, especially for marine life. Most oil spills in the marine environment can form a thin layer on the surface due to the movement of wind, waves, and currents. In this study, the oil spill movement model used the Shallow Water Equation (SWE) model and the equation for the movement of oil spills. The SWE model consists of the equation of mass and momentum derived from the law of conservation of mass which is derived into the equation of continuity and the law of conservation of momentum which is derived into the equation of conservation of momentum. In this model, ocean currents are affected by several disturbances in the form of wind gusts and friction with the bottom. The model is solved numerically through simulation using the finite volume method. Discretization is done by using a staggered grid approach, where the mass and momentum variables are discretized in different cells. From the simulation results, it appears that the movement of oil spills is influenced by wind direction and current. The simulation results also found that the speed of the movement of oil spills has increased in the early times, but then gradually.